Sketches in the history of the Underground Railroad - Pettit, Eber (Open Road Integrated Media, 2015)
True stories drawn from the inspirational and heartrending history of the Underground Railroad It is estimated that by 1850 over one hundred thousand slaves had escaped to freedom in the North via a network of safe houses and secret routes known collectively as the Underground Railroad. First published in 1879, Sketches in the History of the Underground Railroad chronicles the perilous journeys and thrilling adventures of nearly two-dozen escaped slaves and the brave souls who helped them along the way. Compiled by a conductor on the Railroad, these sketches bring the horrors of slavery to vivid life and serve as an enduring testament to the power of the human spirit. This ebook has been professionally proofread to ensure accuracy and readability on all devices.